2019
DOI: 10.24908/pocus.v4i2.13693
|View full text |Cite
|
Sign up to set email alerts
|

Minding the Gap(s): Hospitalists Experience Aspirational, Safety, and Knowledge Deficits That Prevent Them From Practicing POCUS

Abstract: Point-of-care ultrasound (POCUS) has been a mainstay of clinical decision-making in the intensive care unit and emergency department for more than a decade, but adoption into hospital medicine has lagged behind. Recently, internal medicine residency programs have started to develop POCUS curricula for trainees, though concurrent hospitalist training programs have been limited to date, with little consensus on what hospitalist-oriented curricula should entail. As such, there is wide variability amongst hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Despite this, resident POCUS use on hospital medicine wards continues to expand, with studies showing that residents' confidence often exceeds their knowledge 12–14 . Our own previous work uncovered similar supervision and safety gaps, with the majority of faculty lagging behind the trainees they supervise in POCUS knowledge and competence 11 . Meanwhile ultra‐portable ultrasound machines are less expensive and more readily available.…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…Despite this, resident POCUS use on hospital medicine wards continues to expand, with studies showing that residents' confidence often exceeds their knowledge 12–14 . Our own previous work uncovered similar supervision and safety gaps, with the majority of faculty lagging behind the trainees they supervise in POCUS knowledge and competence 11 . Meanwhile ultra‐portable ultrasound machines are less expensive and more readily available.…”
mentioning
confidence: 84%
“…8,9 The deficit in POCUS-trained faculty has been described in several studies and largely attributed to the time, cost, and training barriers that faculty experience. 10,11 Despite this, resident POCUS use on hospital medicine wards continues to expand, with studies showing that residents' confidence often exceeds their knowledge. [12][13][14] Our own previous work uncovered similar supervision and safety gaps, with the majority of faculty lagging behind the trainees they supervise in POCUS knowledge and competence.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, one survey of hospitalists at a single center demonstrated that 16% of providers were using POCUS but only a fraction felt confident in their skill set (both acquisition and interpretation). A large proportion of users had a knowledge deficit regarding accepted uses for POCUS and 21% were using POCUS for uses that are generally not recommended for POCUS examinations such as evaluation of aortic valve disease [ 63 ]. Some hospital medicine programs have established a multi-disciplinary infrastructure to standardize credentialing and ongoing quality assurance.…”
Section: Responsible Use: Ongoing Competency Assessment and Quality Amentioning
confidence: 99%